Chemical technologies for precise protein bioconjugation interfacing biology and medicine. Issue 58 (28th June 2021) - Kumar, Mohan; Reddy, Neelesh C.; Rai, Vishal
Abstract : The methods to regulate the reactivity and various selectivity attributes enable the single-site modification of proteins. Abstract : Proteins provide an excellent means to monitor and regulate biological processes. Hence, a precise chemical toolbox for their modification becomes indispensable. In this perspective, this feature article outlines our efforts to establish the core principles of chemoselectivity, site-selectivity, site-specificity, site-modularity, residue-modularity, and protein-specificity. With the knowledge to systematically regulate these parameters, the field has access to technological platforms that can address multiple challenges at the interface of chemistry, biology, and medicine.